The Study Utilization of Mangosteen (Garcinia mangostana L.) Peel Extract as a Gel-Based Burn Wound Plaster - Kalimaya Qolbi Sani; Paulina Paulina; Priyanka Khansa Insyira (Equilibrium)
Abstract. The industry in Indonesia is currently experiencing significant development dominated by workers in the informal sector. During the business/production processes, problems are often encountered, leading to injuries or wounds. Burn wound are caused by heat sources such as fire, electricity, hazardous chemicals, and radiation. One natural substance with the potential to be used as an alternative treatment for burn wound is mangosteen peel. Mangosteen peel contains active biochemical compounds, including flavonoids, tannins, xanthones, and alkaloid derivatives, which have anti-inflammatory effects that can aid in the wound healing process by promoting collagen formation. Additionally, the presence of saponins in mangosteen peel makes it antibacterial. This research aims to explore the potential of mangosteen peel patches in the healing of burn injuries often experienced by informal industrial workers. The research method used secondary data through a literature review study. Article searches were conducted using keywords such as 'wound' and 'mangosteen peel.' Through the analysis of 10 articles, it was found that mangosteen peel has great potential to be utilized as a mangosteen peel patch, with a wound healing percentage of up to 83% over 21 days at an optimum concentration of 15%. The availability of patches made from mangosteen peel extract (Garcinia mangostana L.) is expected to assist informal workers or UMKM in addressing burn wound they may encounter during work while also helping to utilize waste that would otherwise go unused. Keywords: Biochemical compounds, Burn wound, Informal Sector, Mangosteen Peel, Plaster